First taxonomic revision of the Ptilocephala albida-species group in Europe (Lepidoptera: Psychidae, Oiketicinae) - Arnscheid, W. R.; Weidlich, M. (SHILAP Revista de lepidopterología, 2021)
The European part of the Ptilocephala albida-species group is revised by morphological and molecular characteristics. This supports the existence of six taxonomic separated species in Europe, of which one is described here as new: Ptilocephala rutjani Arnscheid & Weidlich, sp. n. Ptilocephala lorquiniella (Bruand, 1853) “stat. rev”., is again treated as a separate species. In addition, this paper gives an overview on the current status of the revision of the genus Ptilocephala Rambur, 1858 with special emphasis to DNA barcoding.